Evaluation of SeaWiFS and MODIS chlorophyll-a products in the Argentinean Patagonian Continental Shelf (38º S - 55º S) - Dogliotti, Ana Inés; Schloss, Irene Ruth; Almandoz, Gaston Osvaldo; Gagliardini, Domingo Antonio (International Journal of Remote Sensing)
Field measurements of surface chlorophyll-a concentration were used to evaluate for the first time the performance of the standard Moderate Resolution Imaging Spectroradiometer (MODIS) and both standard and regional Sea-viewing Wide Field-of-view Sensor (SeaWiFS) ocean colour algorithms in the Patagonian Continental Shelf (PCS) between 38u S and 55u S. The results showed that the regional algorithms did not significantly improve the global algorithm estimates. Moreover, the SeaWiFS OC4v4 algorithm, National Aeronautics and Space Administration (NASA) standard chlorophyll product, showed the best performance among all the algorithms examined. Nonetheless, all the global and local algorithms analysed showed uncertainties dependent on chlorophyll concentration. Low chlorophyll-a concentration values tended to be overestimated and high values tended to be underestimated. A regional analysis within the PCS showed that higher uncertainties are found in the homogeneous side of the tidal fronts present in the PCS, in areas suggested to be optically complex case 2 waters, while a better result (less bias) was obtained in the southern mid-shelf region. We discuss the probable reasons and provide possible explanations of the regional differences in the performance of the algorithms. Fil: Dogliotti, Ana Inés. Consejo Nacional de Investigaciónes Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Astronomía y Física del Espacio. - Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Astronomía y Física del Espacio; Fil: Schloss, Irene Ruth. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Fil: Almandoz, Gaston Osvaldo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; . Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Gagliardini, Domingo Antonio. Consejo Nacional de Investigaciónes Científicas y Técnicas. Oficina ...